A no a priori knowledge estimation of the impulse response for satellite image noise reduction. Issue 7 (1st April 2015) - Benbouzid, A.B.; Taleb, N.
Abstract Due to launching vibrations and space harsh environment, high resolution remote sensing satellite imaging systems require permanent assessment and control of image quality, which may vary between ground pre-launch measurements, after launch and over satellite lifetime. In order to mitigate noise, remove artifacts and enhance image interpretability, the Point Spread Function (PSF) of the imaging system is estimated. Image deconvolution can be performed across the characterization of the actual Modulation Transfer Function (MTF) of the imaging system. In this work we focus on adapting and applying a no reference method to characterize in orbit high resolution satellite images in terms of geometrical performance. Moreover, we use natural details contained in images as edges transitions to estimate the impulse response via the assessment of the MTF image. The obtained results are encouraging and promising.